Instagram and Digital Media Literacy among Teenagers in Bandung - Rully Khairul Anwar; Ute Lies Siti Khadijah; Edwin Rizal (Communicatus: Jurnal Ilmu komunikasi, 2023)
In a world with the rapid advancement ofdigital media, the ability to manage media content is crucial. The rising influence of social media, particularly from the millennial generation, has significantly transformed how people access information. However, challenges remain; many platforms, such as Instagram, often contain misleading and provocative content. This research was conducted at Madrasah Aliyah Swasta Yasipa in Bandung City. It employed a qualitative approach with a five-month case study.The data wascollected through interviews and observations to assess how well adolescentsacknowledge accurate information on Instagram. The study results show that students can access the features available on Instagram, know and understand the benefits of Instagram, analyze real and hoax information, maintain the ethics of leaving comments on Instagram, and look for verified sources. Therefore, they can analyze what appeals to them, what information is shareable, and what contents require actions. They can produce particular photos, images, videos, and information so that students become more creative when using Instagram.